SUSTAINABILITY INDICATOR FOR ENVIRONMENTAL AND ECOLOGICAL PROTECTION OF AQUATIC SYSTEMS - Argota-Pérez, George (2022)
The aim of the study was to propose a sustainability indicator for the environmental and ecological protection of aquatic systems. A random probabilistic sampling was carried out in the exposure area between the Espinar lagoon and the inner bay of Lake Titicaca, Puno, Perú, where various physical-chemical parameters (PFQ) were determined: dissolved oxygen, pH, total dissolved solids, electrical conductivity, Cu+, Zn+, Pb+, Fe+, Cd+, Al+, Cl-, NO3- and NO2-. Under experimental conditions (water dilution: 10, 20, 30, 40 and 50 ml/1 L), the ecotoxicological effect was evaluated using the biomarker (Bm): reaction time and refuge capacity (TRCR) in Gambusia punctata (Poey, 1854). With the PFQ and the Bm, the sustainability indicator (ISPAEsa) was proposed, which considered five descriptors from a hermeneutic of environmental and ecological economics. For each descriptor, there were three weights (1.0, 0.75 and 0.50) according to the magnitude criteria: high, medium and low. ISPAEsa reported three intervals according to water quality: I) conserved environmental protection: (1.10-1.15; II) non-immediate environmental protection: 1.16-1.30; and III) immediate environmental protection: 1.31-1.50. 76.92% of the PFQ did not comply with the normative value. CRRT was less delayed in the more diluted treatment. The ISPAEsa was 1.4 where immediate environmental treatment is required. It is concluded that the sustainability indicator protects from the environmental and ecological aspects, since it is based on descriptors and biomarkers that allow the analysis of natural conditions.